2021
DOI: 10.5194/bg-2021-46
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High greenhouse gas fluxes from peatlands under various disturbances in the Peruvian Amazon

Abstract: Abstract. Amazonian peat swamp forests remove large amounts of carbon dioxide (CO2) but anaerobic decomposition of the peat produces methane (CH4). Drought or cultivation cuts down on the CH4 production but may increase the CO2 emission. Varying oxygen content in nitrogen-rich peat produces nitrous oxide (N2O). Despite the potentially tremendous changes, greenhouse gas emissions from peatlands under various land uses and environmental conditions have rarely been compared in the Amazon. We measured CO2, CH4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Hergoualc'h et al (2020) identified nitrifier denitrification in the palm swamp. It is a well-documented process in mineralised peats (Wrage-Mönnig et al, 2018;Masta et al, 2020). Anaerobic NH4 + oxidation (anammox) involves nitric oxide (NO) as an intermediate product which could serve as an important substrate for N2O formation by NH4 + oxidisers or denitrifiers (Hu et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hergoualc'h et al (2020) identified nitrifier denitrification in the palm swamp. It is a well-documented process in mineralised peats (Wrage-Mönnig et al, 2018;Masta et al, 2020). Anaerobic NH4 + oxidation (anammox) involves nitric oxide (NO) as an intermediate product which could serve as an important substrate for N2O formation by NH4 + oxidisers or denitrifiers (Hu et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Across the study period, the fluxes correlated log-linearly with soil NH4 + content (Figure 6a). The DNDC model calculates N2O fluxes driven by decomposition of organic N and denitrification following rainfall events (Li et al, 1992). However, more records of N2O peaks after rainfall events are needed to feed a model properly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation